Effect of Phenytoin and Vitamin C on Granulation Tissue Thickness and Total Lymphocyte Infiltration in Enterocutaneous Fistula: In Vivo Study - Iwan Vanca Saragih; Trilaksana Nugroho; Ignatius Riwanto (HM Publisher, 2022)
Background: Enterocutaneous fistula (ECF) is still a problem in the surgical field because it causes high morbidity and mortality. The rate of closure of the ECF without surgical intervention in the evolving era of wound care and with parenteral nutrition has been reported to vary, with most studies showing closure rates in the 20 to 30% range. The administration of phenytoin and vitamin C is expected to be one of the modalities in the non-operative treatment of enterocutaneous fistulas. This study aims to assess the effect of phenytoin and vitamin C on granulation tissue thickness and the amount of lymphocyte infiltration in enterocutaneous fistulas. Methods: This study is an experimental study with a post-test only with a control group design. A total of 24 rats were divided into control groups, P1 (phenytoin+ vitamin c), P2 (phenytoin), and P3 (vitamin c). Histopathological assessment of granulation tissue thickness and lymphocyte infiltration was performed. Data analysis was performed using SPSS with univariate and bivariate methods. Results: The P1 group showed the thickest average thickness of granulation tissue compared to all groups. The P1 group showed a lower number of lymphocyte infiltration cells than all groups. Conclusion: The administration of phenytoin and vitamin C was effective in increasing the thickness of granulation tissue and reducing lymphocyte cells in enterocutaneous fistulas.